Competition and its Impact on Investment in Telecommunications Networks in a Digital Environment - Escobar-Briones, Rebeca; M. Conde-Menchaca, Núbia (Law, State and Telecommunications Review, 2020)
Purpose ”“ The study establishes the determinants of investment in fixed broadband networks and, in particular, to evaluate the impact of economic competition on it, we present a panel model on fourteen countries, including four Latin American. The model uses quarterly data for the period from 2013 to 2018. Methodology ”“ The adopted approach is based on the debate on the relationship between competition and investment, on economic theory, and on findings of studies on the association within investment and competition oriented to European countries and the United States. Findings ”“ Derived from the results, evidence is provided on the existence of a positive relationship between competition and speed of fixed broadband services. The analysis identifies that competition, in services as well as between networks, is favorable for the investment of fixed broadband services. Likewise, the expansion of digital audiovisual entertainment services, the penetration of IoT services, and the higher penetration of mobile broadband, favorably influence investment in networks. Practical Implications ”“ This result provides useful information for policy design in the telecommunications sector. Encouraging network expansion, some regulatory recommendations are to be presented. Additionally, this study provides information for countries that have not been included in this topic, specifically Mexico and others in the Latin American region.